Perilaku Memberikan Saweran kepada Qori atau Qori’ah yang Sedang Melantunkan Ayat Al-Qur’an (Studi terhadap Qur’an Surat Al-A’raf Ayat 204 dalam Perspektif M. Quraish Shihab) - Harahap, Siti Suryani (Lembaga Yasin AlSys, 2023)
This research is included in library research (library research), namely research conducted using literature (library) both in the form of Tafsir Al-Misbah by M. Quraish Shihab., as well as books, theses or journals that study related to reading and listening to the Al-Qur'an 'an. The approach used in this study is the maudhu'i (thematic) interpretation method approach, namely looking at themes related to the etiquette of reading and listening to verses of the Koran. The method used is content analysis, namely analyzing the interpretation of the mufassir figures on verses related to the etiquette of reading and listening to verses of the Qur'an. Based on the results of the research that the writer has done, the writer finds that according to the interpretation of M. Quraish Shihab in the Book of Tafsir Al-Misbah about saweran through the letter verse Qs.al-A'raf: 204, that Allah SWT emphasizes that when the Qur'an is recited, then the order is to listen carefully, and pay attention quietly so that you will receive mercy. So it is forbidden if when the verses of the Qur'an are recited the listeners are busy doing actions that can lead to actions that disturb other people in listening to the Qur'an when it is recited including saweran without commenting on the content and meaning of the verse being recited.